2013
DOI: 10.1371/journal.pone.0060387
|View full text |Cite
|
Sign up to set email alerts
|

Immune Biomarker Differences and Changes Comparing HCV Mono-Infected, HIV/HCV Co-Infected, and HCV Spontaneously Cleared Patients

Abstract: BackgroundImmune biomarkers are implicated in HCV treatment response, fibrosis, and accelerated pathogenesis of comorbidities, though only D-dimer and C-reactive protein have been consistently studied. Few studies have evaluated HIV/HCV co-infection, and little longitudinal data exists describing a broader antiviral cytokine responseMethodsFifty immune biomarkers were analyzed at baseline(BL) and HCV end of treatment follow-up(FU) time point using the Luminex 50-plex assay in plasma samples from 15 HCV-cleared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…Decreasing FGFb levels can be an indication of decreasing fibrotic activity due to IFN‐ α treatment, which has been reported previously . Although many serum biomarker levels decreased significantly as a result of IFN/RBV treatment, previous work by our group indicates that at the end of HCV treatment in those who achieve SVR still have elevated levels of many biomarkers, including inflammatory cytokines compared with those who were exposed to HCV and spontaneously cleared the infection without treatment .…”
Section: Discussionsupporting
confidence: 74%
“…Decreasing FGFb levels can be an indication of decreasing fibrotic activity due to IFN‐ α treatment, which has been reported previously . Although many serum biomarker levels decreased significantly as a result of IFN/RBV treatment, previous work by our group indicates that at the end of HCV treatment in those who achieve SVR still have elevated levels of many biomarkers, including inflammatory cytokines compared with those who were exposed to HCV and spontaneously cleared the infection without treatment .…”
Section: Discussionsupporting
confidence: 74%
“…To balance the risks of type 1 and type 2 errors, the Bonferroni correction was used to correct the individual alpha errors for multiple comparison, using the following significance level for all biomarker analyses: ␣ ϭ 0.05/26 ϭ 0.002. An adjusted P value of Ͻ0.002 was considered significant (22). Differences of cytokine/chemokine levels between plasmas and paired pleural fluid samples were compared using the paired t test.…”
Section: Methodsmentioning
confidence: 99%
“…Although the percent of activated CD4+ and CD8+ T cells and Treg were higher in HIV-infected patients compared to healthy controls, no significant differences were observed among the groups of HIV patients [87]. In a different study, biomarkers of inflammation including INFa were found to be higher in HCV/HIV co-infected patients compared to HCV mono-infected patients but importantly, some decreased after successful sustained virologic suppression (SVR) of hepatitis C [88]. Decreases in sCD163 and sICAM were also noted 24 weeks after HCV treatment with pegylated interferon/ribavirin in another cohort of 54 patients [89].…”
Section: Cryptococcusmentioning
confidence: 99%